Competencies of HRM Graduates Vis-A-Vis Industry Needs: Basis for an Action Plan for Curriculum Enhancement - Delas Peñas, Euniza (JPAIR Institutional Research, 2020)
Hospitality is a fast-changing industry in which educational institutions have to cope with its market demand. Moreover, it was challenging to close the gap between what is taught in the classroom and the industry needs. This study aimed to determine the level of competency of BSHRM graduates and the actual industry needs, which served as the basis for designing an action plan for curriculum enhancement. The mixed-methods research design was used, particularly descriptive survey and in-depth interview method. It involved 100 respondents comprising supervisors and managers and four human resources managers from the industry. Data were analyzed using weighted mean and thematic analysis. Findings revealed that graduates in BS HRM were “highly competent” in all competencies identified in this study, which was also considered “highly needed” by the industry. Moreover, analysis emerged a favorable “attitude” for work was the most important quality that the graduates should acquire and other competencies. Thus, recommendations include strengthening and sustaining the existing competency development training of BS HRM students, integrating the competencies that are highly needed by the industry, and enhancing work attitude by integrating it across the discipline in the curriculum. Furthermore, these recommendations may be considerHRM Graduatesed in crafting the action plan for curriculum enhancement.